Investigating Students' Perspective on English Camp as a Tool to Enhance Communicative Competence - Muhamad Ichsan Al Fauzi; Kiany Leksono; Arsyiezal Laundra Syefianto; Nurul Fadilah Firdaus; Muslimah Susilayati (Universitas Sebelas Maret, 2026)
English language learning in the classroom has become commonplace in efforts to improve the English language skills of each student. In this process, English Camp was introduced, which is English language learning outside the classroom that combines interactive activities with material delivery. This programme is an important contribution to improving communicative skills, especially in the context of English as a foreign language (EFL). This study uses a qualitative case study approach to collect data on students' views on the implementation of English Camp as a programme that contributes to improving English communication skills. The respondents in this study were randomly selected students from X and XI grades of Al-Abidin Bilingual Boarding School (ABBS) Surakarta. Data collection was conducted through in-depth interviews, and data analysis used Creswell's spiral thematic analysis model. The research discussion focused on three main aspects of student experience: cognitive, affective, and psychomotor/conative. Based on findings and discussion in this research, it can be concluded that English Camp provides benefits in improving students' communication skills even though the duration is relatively short. In addition, students' courage and readiness to communicate in English also became more apparent and developed positively.